PENGARUH PARTISIPASI PEJABAT STRUKTURAL DALAM PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI, PROFESIONALISME DAN STRUKTUR ORGANISASI TERHADAP KINERJA MANAJERIAL KABUPATEN MINAHASA UTARA - Maramis, Lidya A.; Saerang, David P. E.; Warongan, Jessy D. L. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
This study aims to determine the effect participation review structural budgetary hearts, and organizational commitment, professionalism, and organizational structure against the boarding costs managerial north minahasa regency. The role of government officials is very important because implementation wheels good governance And Services showed to the society takes with be effective, committed or responsibility, professional and cooperative hearts organizational structure of every government officials through regional work units (SKPD) from the head up subordinate.The population of this research are the 2rd, 3rd, and 4rd echelon of the structural officials on 32 SKPD governments north minahasa regency as many as 701. Samples using Proportional Stratified Random Sampling method , that is random sampling and proportional to the strata. Samples were taken at 10% of the population with a note that the samples taken can represent the population as a whole with a total of 70 respondents.Data analysis method used is multiple linear regression analysis, to test the validity and reliability, Classic assumption test, correlation coefficient, coefficient determination, and hypothesis testing (test f and t), to complete the overall analysis used the software Statistical Product and service Solutio (SPSS) version 20 .The results showed a partial that influence participation structural officers in budgeting significant effect on managerial performance of North Minahasa Regency , for the commitment the organization has no significant effect on the performance of managerial North Minahasa Regency, for professionalism significant effect on managerial performance of North Minahasa Regency, and to the organizational structure significant effect on managerial performance of North Minahasa Regency. And the simultaneous participation of structural officer (X1), organizational commitment (X2), professionalism (X3) and organizational structure (X4) is jointly affect managerial performance of North Minahasa Regency (Y).Keywords:       Participation structural officials in budgeting, organizational commitment, professionalism and organizational structure to managerial performance.